Thermal tolerance of Cydia pomonella (Lepidoptera : Tortricidae) under ecologically relevant conditions - Chidawanyika, Frank (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Agric) (Conservation Ecology and Entomology))--University of Stellenbosch, 2010.